3PC-045 Formulation and stability study of extemporaneous oral liquid dosage forms containing flecainide acetate 2 mg/ml for paediatric use. (March 2019) - Casiraghi, A; Loiacono, S; Bordignon, S; Puzziferri, R; Cilurzo, F; Minghetti, P
Abstract : Background: Flecainide acetate (FlecAc) is an antiarrhythmic drug, effective in children and fetal tachyarrhythmias. FlecAc is commercially available as 50 mg–150 mg oral tablets or intravenous injectable solutions, approved only for use in adults. For paediatric use, an extemporaneous preparation has to be compounded, using the pure active principle or, when this is lacking, the ground tablet. Few examples of extemporaneous FlecAc preparations are reported in the literature, normally at a dose of 20 mg/mL. Nevertheless, in the case of neonates and infants, a lower concentration is useful. Purpose: The aim of this work was to compound FlecAc oral liquids (2 mg/mL) using pure powder (API) or ground commercial tablets (GCT) and to evaluate the chemical stability of the active principle. Material and methods: Oral solutions were compounded using either a preserved simple syrup (PSS) with the addition of a suspending phase or a ready-to-use commercial suspending vehicle, ORA-Plus ORA-Sweet (OPOS), to be stored at 4°C or 25°C, respectively. Four types of aqueous solutions were compounded following hospital standard operating procedures. In three different pharmacies, seven hospital pharmacists compounded a total of 28 preparations (n=28): 1) PSS-API, 2) PSS-GCT, 3) OPOS-API and 4) OPOS-GCT. The samples were stored at 4°C (PSS), 25°C (OPOS) and 40°C (both) for 42 days. The FlecAc content was determined using a stability indicating the high-performance liquid chromatography method. Results: At time t=0, the mean FlecAc content of all samples was 1.82±0.10 mg/mL, against a labelled content of 2.00 mg/mL. A significant difference in FlecAc content was observed only in the case of GCT preparations (OPOS-GCT: 1.87±0.07 mg/mL; PSS-GCT: 1.79±0.15 mg/mL, p=0.03). Based on these results, duration and method of stirring were further investigated and improved in a second batch, which showed a higher mean content and reduced variability (1.92±0.06 mg/mL). FlecAc was stable over the entire period. Conclusion: FlecAc is completely solubilised in the proposed vehicles and stable for 42 days. A suspending agent is therefore necessary only to mask the excipients of the tablet, if not completely solubilised. Normally suggested storage in a refrigerator when PSS is compounded should be carefully considered, because of the influence of the reduced temperature on FlecAc solubility. References and/or acknowledgements: No conflict of interest.